Subjective Normsand Entrepreneurship Education Towards Self-Efficacy and Entrepreneurship - Ariyanto Masnun; Chintya Ones Charli; Budi Hartoyo; Rahmadani Hidayat; Menhard Menhard (DINASTI RESEARCH, 2023)
Setih Setio Muara Bungo Institute of Administration and Health prepares students to become independent and successful entrepreneurs of the future. The purpose of this research is to clarify whether there is a subjective norm in entrepreneurship education regarding self-efficacy in entrepreneurship among students of the Faculty of Management in the business administration course in the eighth semester. Methods of collecting literature review data and field his research, including interviews, observations, and questionnaires conducted on a student population and her sample of 75 people. The data analysis method used to test the hypotheses in this study is SEM-PLS. As a result of testing the direct influence hypothesis, it was shown that entrepreneurship education has a significant impact on self-efficacy, entrepreneurship education has a significant impact on entrepreneurship, and entrepreneurship education has a significant impact on entrepreneurship. I was. I was. However, subjective norms do not significantly influence entrepreneurial intentions.